2011
DOI: 10.1016/j.bbi.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

An IL-1 receptor antagonist blocks a morphine-induced attenuation of locomotor recovery after spinal cord injury

Abstract: Morphine is one of the most commonly prescribed medications for the treatment of chronic pain after a spinal cord injury (SCI). Despite widespread use, however, little is known about the secondary consequences of morphine use after SCI. Unfortunately, our previous studies show that administration of a single dose of morphine, in the acute phase of a moderate spinal contusion injury, significantly attenuates locomotor function, reduces weight gain, and produces symptoms of paradoxical pain (Hook et al., 2009). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 58 publications
4
54
0
Order By: Relevance
“…In the absence of norBNI, morphine-treated rats showed decreased locomotor recovery relative to vehicle-treated controls, replicating our previous studies. 2,4 Moderate to high doses of norBNI (0.08 and 0.32 lmol respectively), however, blocked the effects of morphine on locomotor recovery. Importantly, at these doses, morphine administration still produced significant analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of norBNI, morphine-treated rats showed decreased locomotor recovery relative to vehicle-treated controls, replicating our previous studies. 2,4 Moderate to high doses of norBNI (0.08 and 0.32 lmol respectively), however, blocked the effects of morphine on locomotor recovery. Importantly, at these doses, morphine administration still produced significant analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] To address this, norBNI was administered as an adjuvant to morphine treatment 24 h following SCI, and locomotor recovery was monitored for a 21 day period. Locomotor scores collected before treatment on day 1 did not differ significantly across groups (F [7, Fig.…”
Section: Recovery Of Locomotor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a clinically used compound or one of its metabolites possesses such TLR agonistic activity, side effects of the drug may be attributable to such undefined TLR agonist activity. In the case of opioids, such opioid-induced central immune signaling contributes to adverse recovery in preclinical models of spinal cord injury (Hook et al, 2009(Hook et al, , 2011. Moreover, the shared central immune signaling properties of opioids with other drugs of abuse, such as methamphetamine, also raise the possibility that this drug-induced central immune signaling process may be a common phenomenon across drugs of abuse, resulting in amplification of drug-mediated activation of the mesolimbic dopamine reward pathway.…”
Section: What Are the Broader Implications Of Xenobiotic-induced Cmentioning
confidence: 99%
“…[5][6][7] Moreover, these adverse effects are not limited to IT morphine administration. Woller and colleagues 8 showed that self-administration of high doses of intravenous (IV) morphine, a more clinically relevant route of administration, also significantly undermined locomotor recovery after injury.…”
mentioning
confidence: 99%